2018
DOI: 10.3389/fnmol.2018.00339
|View full text |Cite
|
Sign up to set email alerts
|

Potential Roles of microRNAs in the Regulation of Monoamine Oxidase A in the Brain

Abstract: Monoamine oxidase A (MAO-A) is an enzyme that regulates the levels of monoamine neurotransmitters, such as serotonin, noradrenaline and dopamine and it has been used as a therapeutic target for depression. However, MAO-A inhibitors, which directly acts on MAO-A protein, have limited use due to their adverse effects. microRNAs (miRNAs) are 18–22 nucleotide long, small non-coding RNAs, which have recently emerged as regulators of protein levels that could potentially be new therapeutic targets for psychiatric di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 108 publications
(142 reference statements)
0
11
0
Order By: Relevance
“…The hemolysis in serum was determined by the absorbance of hemoglobin at 414 nm (A414) using NanoDrop ND-1000 (Thermo Fisher Scientific, Waltham, MA, USA). Serum samples with absorbance ≤0.3 were considered as unhemolyzed [ 40 ], and stored at −80 °C until further purification ( Table S7 shows A414 for each sample).…”
Section: Methodsmentioning
confidence: 99%
“…The hemolysis in serum was determined by the absorbance of hemoglobin at 414 nm (A414) using NanoDrop ND-1000 (Thermo Fisher Scientific, Waltham, MA, USA). Serum samples with absorbance ≤0.3 were considered as unhemolyzed [ 40 ], and stored at −80 °C until further purification ( Table S7 shows A414 for each sample).…”
Section: Methodsmentioning
confidence: 99%
“…Several miRNAs have been identified as important therapeutic targets involved in synaptic plasticity and neuro-development (27). The targeting of Ca 2+/ calmodulin kinase II (CaMKII) by miR-219 negatively regulates arsenic-induced hippocampus structural damage and the causes impairment of memory and learning (28).…”
Section: Introductionmentioning
confidence: 99%
“…The time course of recovery of activity after smoking cessation extends over several weeks after smoking cessation, consistent with the equivalent recovery time from inhibition by known irreversible MAO inhibitory drugs ( Fowler et al, 2003 ). Although epigenetic ( Launay et al, 2009 ) and microRNA ( Higuchi et al, 2018 ) mechanisms for MAO activity reduction have been suggested, direct inhibition by components of tobacco smoke as the major cause of the observed reduction remains a likely mechanism by which MAO inhibition is accomplished in smokers.…”
Section: Monoamine Oxidase Inhibitorsmentioning
confidence: 99%